Biologi Penghisap Buah Helopeltis sp. (Hemiptera: Miridae) pada Buah Kakao dan Mentimun - Nelly, Novri; Khairul, Ujang (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2017)
This research purposed to study biology of Helopeltis sp. on cocoa and cucumber fruits. Research was done in insect bioecology laboratory using direct observation with 10 replications for each fruit. Parameter observed were copulation (hours), preoviposition time (days), number of eggs, nymphals, and adult periods (days), Oviposition time (days), and post oviposition time (days). The data obtained were analyzed descriptively and compared with t-test. Result of this research showed that Helopeltis sp. could thrive in cacao and cucumber fruits. Adult of Helopeltis sp. longevity in cacao fruits was 16 days and in cucumber fruits was 13 days. The number of eggs product average 10-10.9 eggs/female.